2016
DOI: 10.1002/jclp.22415
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Burdensomeness in Older and Younger Adults: Evaluation of the Psychometric Properties of the Interpersonal Needs Questionnaire

Abstract: This study provides marginal support for measurement invariance of the INQ-15 Perceived Burdensomeness subscale across younger and older adults, but results also suggest age differences in the perceived burdensomeness construct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Second, given that our sample was comprised of young adults, we were unable to examine invariance based on age. Prior studies have demonstrated that the INQ exhibited invariance across age groups (Lutz & Fiske, 2017; Van Orden et al, 2012), but it will be important to replicate this in a sexual minority sample. Third, there are several versions of the INQ and our findings are specific to the 15-item version.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, given that our sample was comprised of young adults, we were unable to examine invariance based on age. Prior studies have demonstrated that the INQ exhibited invariance across age groups (Lutz & Fiske, 2017; Van Orden et al, 2012), but it will be important to replicate this in a sexual minority sample. Third, there are several versions of the INQ and our findings are specific to the 15-item version.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a sample of 539 youth, Hill et al (2020) found that the 12-item version of the INQ demonstrated strong invariance across race/ethnicity (White, Black, and Latinx groups) and across male and female youth (gender identity was not reported). A majority of recent psychometric testing of the INQ has focused on measurement invariance across age groups (Lutz & Fiske, 2017), and the properties of translated versions of the scale (e.g., Lai & Boag, 2021, who assess the properties of the Chinese version of the INQ and test invariance across Chinese and Australian cultures). There is a need for researchers to continue to assess the invariance of the INQ across different populations, particularly those with high rates of suicide, such as sexual minority individuals (King et al, 2008), as better understanding of invariance, or lack thereof, helps increase the precision and validity with which we can link thwarted belongingness and perceived burdensomeness to suicidal thoughts and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The Interpersonal Needs Questionnaire assesses suicidal desire through two subscales: Perceived Burdensomeness (6-items; internal consistency ranging from α = 0.84 to α = 0.94 with older adult sample; Lutz & Fiske, 2016), and Thwarted Belongingness (9-items; internal consistency from α = 0.81 to α = 0.87; Hill et al, 2015) which are included in the IPTS theory and together encapsulate suicide desire. Each item is scored on a 7-point Likert-type scale, in which 1 represents “not true at all for me” and 7 represents “very true for me.” Sample items include “These days, the people in my life would be better off if I were gone,” (PB) and “These days, I often feel like an outsider in social gatherings” (TB).…”
Section: Methodsmentioning
confidence: 99%
“…Future studies can bring further implications from gathering additional information such as socioeconomic differences and health conditions to explain factors that exacerbate racial disparities. Finally, the instrument used to measure suicidal desire was originally normed on young adults, although measurement invariance research suggests the instrument is appropriate to use with older adults as well (Lutz & Fiske, 2016).…”
Section: Limitationsmentioning
confidence: 99%
“…1 First, perceived burdensomeness is an individual's self-view that they are a problem or defective in a way that burdens the people in their life. Greater perceived burdensomeness is a robust predictor of suicidal ideation and behavior (Christensen, Batterham, Soubelet, & Mackinnon, 2013;Joiner et al, 2002;Lutz & Fiske, 2016;Van Orden, Lynam, Hollar, & Joiner, 2006;Van Orden et al, 2008). Self-concealment is linked to perceived burdensomeness because individuals are thought to self-conceal, in part, to avoid burdening others (Larson & Chastain, 1990).…”
Section: Self-concealment and Unmet Interpersonal Needsmentioning
confidence: 99%